2005
DOI: 10.1002/chem.200400852
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Attack on Sulfur–Sulfur Bonds: Coordination of Lithium Cations to Sulfur‐Rich Molecules Studied by Ab Initio MO Methods

Abstract: Complex formation between gaseous Li+ ions and sulfur-containing neutral ligands, such as H2S, Me2Sn (n = 1-5; Me = CH3) and various isomers of hexasulfur (S6), has been studied by ab initio MO calculations at the G3X(MP2) level of theory. Generally, the formation of LiS(n) heterocycles and clusters is preferred in these reactions. The binding energies of the cation in the 29 complexes investigated range from -88 kJ mol(-1) for [H2SLi]+ to -189 kJ mol(-1) for the most stable isomer of [Me2S5Li]+ which contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
17
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 66 publications
7
17
0
Order By: Relevance
“…However, in our previous work we have shown that the sulfur homocycles S 6 , [45] S 7 , [46] and S 8 [47] form chelate complexes of the type [MS n ] + with univalent metal cations such as Li + , Ca + , V + , and Cu + . The last three metal ions are even able to break down the S 8 molecule to form complexes with two S 4 ligands which are more stable than the isomeric S 8 complexes.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, in our previous work we have shown that the sulfur homocycles S 6 , [45] S 7 , [46] and S 8 [47] form chelate complexes of the type [MS n ] + with univalent metal cations such as Li + , Ca + , V + , and Cu + . The last three metal ions are even able to break down the S 8 molecule to form complexes with two S 4 ligands which are more stable than the isomeric S 8 complexes.…”
mentioning
confidence: 98%
“…Previously, we have shown that the methyl derivatives Me 2 S n with n = 2-5 form chelate complexes with Li + ions. [45] In these cases the interaction energy ranges from À140 to À190 kJ mol À1 and the bonding has been explained by iondipole attraction after the metal cation induced or enhanced the dipole moment of the polysulfide ligand by polarization. A similar interaction can be expected with the positively charged zinc atoms at the surface of ZnO.…”
mentioning
confidence: 98%
“…We did not intend to scan the total PES of this system. Instead, using existing knowledge of the various isomers of [LiS 6 ] + [11] we investigated mainly the coordination of Li + to the previously studied isomeric cyclic forms of S 8 and to only one of the eight- Figure 1. Various cyclic and chain-like isomers of the S 8 molecule with relative energies (kJ·mol -1 ) and symmetries (according to ref.…”
Section: Introductionmentioning
confidence: 99%
“…[11] In this work we have investigated theoretically the interaction of the sulfur homocycle S 8 with gaseous Li + which serves as a simple model ion to allow calculations at a high level of theory. Besides S 6 , [11] only the coordination of gaseous S 3 to Li + has been investigated previously by quantum-chemical calculations: [LiS 3 ] + is of C 2v symmetry. [12] In the case of [LiS 6 ] + , 15 isomeric structures have been identified on the potential energy hypersurface (PES).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation